Occupational Health and Safety in the Turkish Fisheries and Aquaculture; a Statistical Evaluation on a Neglected Industry - Ozan Soykan (Elsevier, 2023)
Background: Fisheries and aquaculture are statistically acknowledged to be among the most dangerous occupations. Yet, industrial safety and health precautions against occupational accidents within the sector are not sufficiently implemented in many parts of the world. The present study aims to provide a quantified overview of work accident statistics in the Turkish fisheries and aquaculture industry. Methods: This article presents an overview of reported injuries and fatalities in the Turkish fisheries and aquaculture industries from 2006 to 2020. Incident, permanent incapacity, and fatality rates were calculated, and the difference between fisheries and aquaculture was statistically examined. Results: The overall incident, permanent incapacity, and fatality rates were 449.4, 4.7, and 5.7 per 100,000 worker years, respectively, over the 15-year period. With these fatality rates, fisheries and aquaculture are two of the industries with the highest fatality rates among comparable industries in Turkey. Incident rates in fisheries and aquaculture indicated that aquaculture work is more dangerous and risky. The data set includes 25 fatalities and 22 permanent incapacity cases over 15 years and shows an increase in fatality rates and occupational accidents in the last 8 years. Conclusion: present study showed that the quality of data and reporting in the Turkish fisheries and aquaculture industries including occupational illnesses, must be improved in order to be more preventative and to develop efficient safety management in the sector. Incentives for providing thorough data on occupational incidents must be enhanced to improve occupational safety awareness in Turkish fisheries and aquaculture.